Is Liver Cirrhosis a Risk Factor for Osteonecrosis of the Femoral Head in Adults? A Population-Based 3-Year Follow-Up Study - Hsieh, Yu-Hsi; Tseng, Kuo-Chih; Tsai, Chen-Chi; Tsai, Chih-Chun; Tseng, Chih-Wei; Hung, Tsung-Hsing (Internal Medicine, 2011)
Background The relationship between osteonecrosis of the femoral head (OFH) and liver cirrhosis is controversial. The aim of this study was to determine whether liver cirrhosis is associated with the occurrence of OFH. Methods We used the National Health Insurance Database, derived from the Taiwan National Health Insurance program. The study cohort comprised 40,769 adult patients with liver cirrhosis. The comparison cohort consisted of 40,769 randomly selected age- and sex-matched subjects. Results During the 3-year follow-up period, there were 321 (0.8%) cirrhotic patients with OFH, and 126 (0.3%) non-cirrhotic patients with OFH (p<0.001). Cox's regression analysis, adjusted by the patients' age, sex, and other confounding factors, showed that the cirrhotic patients had a higher risk for occurrence of OFH than non-cirrhotic patients during the 3-year period (hazard ratio=2.38, p<0.001). In this 3-year study, the incidence density of cirrhotic patients hospitalized for OFH was 3 episodes/1,000 person-year. Conclusion We conclude that cirrhotic patients have a higher risk for occurrence of OFH than non-cirrhotic patients.